The measurement of family process variables: The effect of adolescent and parent perceptions of family life on delinquent behavior - Krohn, Marvin D. (Journal of quantitative criminology, 1992)
Both adolescent and parental perceptions of how family members interact with and feel about one another are examined to determine their relationship to official and self-reported delinquent behavior. Consistent with prior research, adolescent perceptions of family processes were weakly related to those of their parents. Both parental and adolescent family process measures made independent and significant contributions to the explanation of self-reported and official delinquent behavior. Parental measures contributed more to the explanation of official data than did adolescent measures when compared to the results for self-reported delinquency. Methodological and substantive reasons for these findings are discussed. The importance of taking into account parental perceptions of family interaction, as well as the perceptions of adolescents, is emphasized.